Intellectual property : a very short introduction - Vaidhyanathan, Siva (Very short introductions, 2017)
" We all create intellectual property. We all use intellectual property. Intellectual property is the most pervasive yet least understood way we regulate expression. Despite its importance to so many aspects of the global economy and daily life, intellectual property policy remains a confusing and arcane subject. This engaging book clarifies both the basic terms and the major conflicts surrounding these fascinating areas of law, offering a layman's introduction to copyright, patents, trademarks, and other forms of knowledge falling under the purview of intellectual property rights. Using vivid examples, noted media expert Siva Vaidhyanathan illustrates the powers and limits of intellectual property, distilling with grace and wit the complex tangle of laws, policies, and values governing the dissemination of ideas, expressions, inventions, creativity, and data collection in the modern world. Vaidhyanathan explains that intellectual property exists as it does because powerful interests want it to exist. The strongest economies in the world have a keen interest in embedding rigid methods of control and enforcement over emerging economies to preserve the huge economic interests linked to their copyright industries-film, music, software, and publishing. For this reason, the fight over the global standardization of intellectual property has become one of the most important sites of tension in North-South global relations. Through compelling case studies, including those of Starbucks, Coca-Cola, Sony, Amazon, and Google Books, Vaidhyanathan shows that the modern intellectual property systems reflect three centuries of changes in politics, economics, technologies, and social values. Although it emerged from a desire to foster creativity while simultaneously protecting it, intellectual property today has fundamentally shifted to a political dimension. "--